Sonological Evaluation of Ectopic Pregnancy-an Analysis of 50 Cases (Medicine Today, 2022)
Introduction: Ectopic pregnancy is the implantation of a fertilized egg in a location outside of the uterine cavity, including the fallopian tubes, cervix, ovary, cornual region of the uterus, and the abdominal cavity.Objective: To evaluate the sonological findings of ectopic pregnancy.Materials and Methods: A descriptive study was carried out at ultrasound unit in Lab-Aid diagnostic, Comfort Medical Services and Green View Diagnostic Complex in Sylhet city between January 2012 to January 2014. We included all cases with confirmed diagnosis of ectopic pregnancy, all antenatal mothers who are present in antenatal unit in a selected Hospital and excluded mothers with other associated medical condition.Results: Common clinical pattern were shock, marked pallor ness, abdominal pain, amenorrhea and irregular vaginal bleeding 52%, 66%,62%,54% and 38% respectively. Risk factor of ectopic pregnant in this study, 40% had history of infertility, 06% had Non tuberculous PID, 70% had no risk factor, 04% had tuberculous PID, 14% had previous abdominal pelvic surgery, 18% had previous ectopic and 10% had endometriosis.Conclusion: Common clinical pattern were shock, marked pallor ness, abdominal pain, amenorrhea and irregular vaginal bleeding. History of infertility, Non tuberculous PID, no risk factor, tuberculous PID, previous abdominal pelvic surgery, previous ectopic and endometriosis were risk factor of ectopic pregnant in this study.Medicine Today 2022 Vol.34(1): 75-78